AJARAN TOLERANSI DAN PENDIDIKAN MULTIKULTUR DALAM LONTAR BUBUKSAH - I Made Suweta (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2019)
Based on this background, there are two issues to be discussed namely: how are the teachings of tolerance and multi-cultural education in the Bubuksah manuscript? In Bubuksah story there appears a universal value, tolerance and multicultural education, where the attitude of tolerance is seen in the Crow Crow who are accustomed to living side by side with their siblings, even though they differ in spiritual practice. Likewise, multicultural education, views that every human being should be able to co-exist together, because difference is a gift from God.